2020
DOI: 10.3390/ijerph17218056
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Profile: ZOE 2.0—A Community-Based Genetic Epidemiologic Study of Early Childhood Oral Health

Abstract: Early childhood caries (ECC) is an aggressive form of dental caries occurring in the first five years of life. Despite its prevalence and consequences, little progress has been made in its prevention and even less is known about individuals’ susceptibility or genomic risk factors. The genome-wide association study (GWAS) of ECC (“ZOE 2.0”) is a community-based, multi-ethnic, cross-sectional, genetic epidemiologic study seeking to address this knowledge gap. This paper describes the study’s design, the cohort’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…The initial study population comprised 300 preschool-age children attending public preschool (Head Start) centers in North Carolina, participants of a community-based, cross-sectional, epidemiologic study (ZOE 2.0) of early childhood oral health (Divaris and Joshi 2020; Divaris et al 2020). Children were between 36 and 71 mo old.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial study population comprised 300 preschool-age children attending public preschool (Head Start) centers in North Carolina, participants of a community-based, cross-sectional, epidemiologic study (ZOE 2.0) of early childhood oral health (Divaris and Joshi 2020; Divaris et al 2020). Children were between 36 and 71 mo old.…”
Section: Methodsmentioning
confidence: 99%
“…Children underwent comprehensive dental examinations recording dental caries experience using International Caries Detection and Classification System (ICDAS) criteria by trained and calibrated examiners between August 2016 and February 2019. Detailed descriptions of the clinical examination (Ginnis et al 2019), biofilm collection, and analysis protocols (Divaris et al 2019), as well as the parent study’s cohort profile (Divaris et al 2020), have been reported in detail in previous publications.…”
Section: Methodsmentioning
confidence: 99%
“…To understand the distributional characteristics of metatranscriptomics data, in Section 3 we introduced data collected from a genetic-epidemiologic study of early childhood oral health (the "ZOE 2.0" study) [27,28] wherein oral microbial metatranscriptomics data were generated for approximately 300 children aged 3-5 years. We also introduced a gut microbial transcriptome dataset to study inflammatory bowel diseases [7].…”
Section: Outlinementioning
confidence: 99%
“…In the following section, we describe the microbiome and metabolome data used for the new method development and application, alongside the three contributing studies. ZOE 2.0 study data ZOE 2.0 is a community-based molecular epidemiologic study of early childhood oral health in North Carolina (11,12). The study collected clinical information on preschool-age children's (ages 3-5) dental cavities (i.e., referred to early childhood caries or ECC) (13) and supragingival biofilm samples from a sample of over 6,000 children (14).…”
Section: Cohort and Data Descriptionmentioning
confidence: 99%
“…The study collected clinical information on preschool-age children's (ages 3-5) dental cavities (i.e., referred to early childhood caries or ECC) (13) and supragingival biofilm samples from a sample of over 6,000 children (14). A subset of participants' biofilm samples underwent metagenomics, metatranscriptomics, and metabolomics analyses, under the umbrella Trans-Omics for Precision Dentistry and Early Childhood Caries or TOPDECC (accession: phs002232.v1.p1) (11). As such, metagenomics (i.e., shotgun whole genome sequencing or WGS), metatranscriptomics (i.e., RNA-seq), and global metabolomics data (i.e., ultra-performance liquid chromatography-tandem mass spectrometry) (5,15,16) from supragingival biofilm samples of ~300 children, paired with clinical information on ECC are available.…”
Section: Cohort and Data Descriptionmentioning
confidence: 99%